1999
DOI: 10.1364/josaa.16.001229
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance and curvature of the inner limiting membrane at the foveola

Abstract: Light reflected specularly by the inner limiting membrane (ILM) provides information on the topography of the retinal surface. The ILM in the central part of the foveal pit acts as a concave mirror. Light reflected specularly by this mirror forms an image of the entrance pupil in front of the retina. In 15 normal subjects (ages 16-56 years) we have measured photometric and geometrical-properties of this image to derive two characteristics of the ILM: its reflectance rho at the foveola and its radius of curvatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Several studies have suggested that there may be age-related change in foveal architecture, and that could be relevant to the changes in photopigment OD distribution that we have observed (Elsner et al, 1998;Gorrand & Delori, 1999). Alpern (1979) suggested that perhaps "cone outer segments may be growing longer as subjects grow older" (p. 99).…”
Section: Photopigment Od and Normal Agingmentioning
confidence: 55%
“…Several studies have suggested that there may be age-related change in foveal architecture, and that could be relevant to the changes in photopigment OD distribution that we have observed (Elsner et al, 1998;Gorrand & Delori, 1999). Alpern (1979) suggested that perhaps "cone outer segments may be growing longer as subjects grow older" (p. 99).…”
Section: Photopigment Od and Normal Agingmentioning
confidence: 55%
“…A more parallel alignment of the photoreceptor axons with respect to the imaging light would result in a reduction of phase retardation along that axis. A reduction in the lateral displacement of these central photoreceptor axons would cause an age-associated shallowing of the foveal pit, as demonstrated with reflectivity maps of the foveal depression (Gorrand & Delori, 1999). Changes of this nature would also be expected to cause a decrease in the centerpoint macular thickness, also consistent with recent findings of macular thinning with age (Song et al, 2010), although changes with age in macular thickness are inconsistent among laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reflection at the ILM is specular and therefore directional, it does illuminate the pupil quasi-uniformly and can therefore be treated as nondirectional because it emanates from an image of the source located very close to the retina. 22 Next, the only directional reflection takes place at the cone outer segments. A further nondirectional reflection occurs at the retinal pigment epithelium.…”
Section: Overviewmentioning
confidence: 99%